Kinin B1 Receptor Agonist Enhances Blood-Brain Barrier Permeability in Healthy and Glioblastoma Environments - Carolina Batista; João Victor Roza Cruz; Michele Siqueira; João Bosco Pesquero; Joice Stipursky; Fabio de Almeida Mendes (Pharmaceuticals)
Background/Objectives: The low permeability of the blood-brain barrier (BBB) represents a significant challenge to effective systemic chemotherapy for primary and metastatic brain cancers. Kinin receptors play a crucial role in modulating BBB permeability, and their agonist analogs have been explored in preclinical animal models to enhance drug delivery to the brain. In this study, we investigated whether des-Arg9-bradykinin (DBK), a physiological agonist of kinin B1 receptor (B1R), acts as a brain drug delivery adjuvant by promoting the transient opening of the BBB. Methods: Human brain microvascular endothelial cells (HBMECs) were treated with DBK in the culture medium and in conditioned media from glioblastoma cell lines, namely T98G (CMT98G) and U87MG (CMU87). Immunofluorescence, RT-qPCR, in-cell Western assay, and proximity ligation assay (PLA) were performed to analyze BBB components, kinin receptors and TLR4, a receptor associated with the kinin pathway and inflammation. The effect of DBK on enhancing paracellular molecule transport was evaluated using Evans blue dye (EB) quantification in a cell culture insert assay and in an in vivo model, where mice with and without brain tumors were treated with DBK. To assess the functional impact of the transient BBB opening induced by DBK, the chemotherapeutic drug doxorubicin (DOX) was administered. Results: Treatment with DBK facilitates the presence of EB in the brain parenchyma by transiently disrupting the BBB, as further evidenced by the increased paracellular passage of the dye in an in vitro assay. B1R activation by DBK induces transient BBB opening lasting less than 48 h, enhancing the bioavailability of the DOX within the brain parenchyma and glioma tumor mass. The interaction between B1R and TLR4 is disrupted by the secreted factors released by glioblastoma cells, as conditioned media from T98G and U87 reduce TLR4 staining in endothelial cells without affecting B1R expression. Conclusions: These results further support the potential of B1R activation as a strategy to enhance targeted drug delivery to the brain.